Development of a robotic vision system with a modular architecture - Santos, Joaquim Vasco Oliveira dos (2015)
Vision systems are becoming a very active research area and rapidly changing with new applications arising more and more. Applications using image processing are getting common as time moves forward, and applications such as converting documents to text, cameras detecting faces and people smiling, object recognition among others are found in daily objects such as cameras and phones. With the development of vision systems, robotics is an area that can bene t a lot more from abilities such as object detection and information extraction such as object position and orientation. The purpose of this thesis is the development of a modular vision system to be used by the robotic soccer players of team CAMBADA, participant in the robocup Middle Size Leage (MSL). The modular vision system is also easily exported onto other robotic projects that possess vision, a way of seeing the world around them. The vision system will possess modules with speci cs tasks such as inage acquisition and object detection, visual debug and remote con guration of the inherent system parameters. The vision system will use the UAVision library to acquire images and information extraction. A remote application to interact and con gure the vision system was also developed using the Qt4 application programming interface. This remote application will interact with the server module of the modular vision system through the network using the transmission control protocol. In order to transfer images and parameters of the vision system a library was developed to handle the transmission control protocol using as base the POSIX sockets application programming interface. This library is used in the modular vision system server as well as in the remote application. The main objectives of this thesis have been accomplished and part of this work is already being used by the CAMBADA team.